A Proposed contemporary worship and training center of Jesus Christ Antioch church - Talastas, Joshua Joel B. (Manila : National University, 2016)
The researcher observed and interviewed the members, attendees and leaders of the Antioch Church. The best solution for the church congregation is to have a big church is the major road that can accommodate the increasing numbers and can win more people for Christ.
Chapter 1. The Problem and it's settings -- Chapter 2. Research Methodology -- Chapter 3. Terms and Reference -- Chapter 4. Data Gathering, Collection and Analysis of Data -- Chapter 5. Design Framework -- Chapter 6. Translations -- Bibliography -- Appendices.
Includes bibliographical references.
Keywords: CHURCH HISTORY